Perceived Partner Confirmation, Depression Management Efforts, and Relationship Functioning in Committed Romantic Relationships. Issue 3 (27th May 2022) - Zhong, Lingzi; Wang, Yiwei; Dailey, René M.
Abstract : Drawing upon confirmation theory, this study investigated the associations among perceived partner confirmation, depressed individuals' perceived partner confirmation, depression management efforts (DMEs), relationship satisfaction, and conflicts in committed romantic relationships. Regression analyses ( n = 222) suggested that perceived partner acceptance related to greater relationship satisfaction and fewer conflicts. Perceived partner challenge was associated with greater DMEs, greater relationship satisfaction, but more conflicts. The combination of perceived acceptance and challenge was associated with greater DMEs and more conflicts. Lastly, depression severity moderated the association between DMEs and perceived partner confirmation. Results offered insights into how romantic partners could facilitate DMEs while maintaining relationship quality.